Comparación entre consumos de agua potable durante la cuarentena del 2020 y registros históricos en poblaciones de Chimborazo y Cañar - Chávez Cedillo, Katherine Elizabeth (2022)
The worldwide COVID 19 forced the governments of the different countries to opt for measures such as mandatory quarantine to stop the contagion. Ecuador assumed this measure on March 17th, 2020, bringing changes in various habits, including the consumption of drinking water; under these circumstances, the hypothesis was raised, during the quarantine, the maximum consumption occurs. To corroborate the theory, consumption records were compiled in two towns in Cañar and eight in Chimborazo, corresponding to the months of quarantine and previous years in order to compare them. In addition, it was lost that, for the sizing of new water systems or expansions, the Ecuadorian Code of Practice CPE INEN has been applied, which has not been updated. Code establishes that a consumption variation factor Kd is used to determine the maximum daily flow, according to a range or extreme to studies of existing drinking water systems. Based on the historical records obtained from existing systems, the consumption coefficient Kd will be determined for each population under investigation. The study was developed applying a statistical analysis; the data was manually refined; later, they were transferred to the Minitab 19 software applying normality and homoscedasticity test determining the data distribution. An ANOVA and Tukey analysis of variance was performed, which was able to determine if there is a significant difference between the means of the data. It was obtained that the city of Cañar presented its maximum historical consumption in June (2020), while the other populations presented high consumption in the quarantine months. However, they are not the maximum of their historical record. In addition, the reasons for the variation in consumption in the different populations are indicated, and the calculation of the consumption coefficient of each of the people is compared with the regulations